Training and Making Avocado Seed Flour as Snack Food in Dalu Sepuluh Village Tanjung Morawa Residence - bakara, tiar lince; Rumida; Siahaan, Ginta (Journal of Saintech Transfer, 2019)
Avocado seeds are waste that can be utilized by the community while the seeds are only disposed of as waste. Avocado seeds have a hypoglycemic effect, an antidiabetic effect through its ability to reduce blood glucose levels and contain high enough starch by 23%. The high starch content allows the use of avocado seeds into flour. The avocado seed flour produced will be applied for making donuts, cookies and simulation chips. The aim of this Community Service is to provide knowledge to the women cadres group and mothers in the hope of being able to turn avocado seeds into avocado seed flour and be processed into snack foods such as cookies, donuts and simulated chips. Management of Community Service is carried out in Dalu Sepuluh-B Village, Tanjung Morawa Sub-district. The Community Service method is by demonstration and training so that women group and mothers are able and skilled at making avocado seed flour into donuts, cookies and simulated chips. The results of community service activities are that participants of the cadre group and PKK mothers have known the benefits of avocado seed flour and have been skilled in making processed products from avocado seed flour that can be applied in the community so that it can improve the degree of public health.